The WTO: crossing the borders of intergovernamentalism - Correa, Ana María (2016)
This article analyzes the Resolution Dispute System of the World Trade Organization (WTO) using the lens of governance and supra-nationality. It places particular attention on the WTO' s capacity to become an omnipotent entity, not dependent on any State in particular, but which, at the same time, must work to assure the adequate enforcement of its decisions with members.